Gender Equality and Women’s Empowerment in Asia and the Pacific - United Nations Economic; Social Commission for Asia; the Pacific (United Nations, 2016)
This publication provides a regional overview of progress made in implementation of the Beijing Declaration and Platform for Action in the Asia-Pacific region, from the perspectives of the national governments. More specifically, this report provides a summary of the identified achievements and challenges of ESCAP members and associate members in relation to gender equality and women’s empowerment, including in relation to the 12 critical areas of concern of the Platform for Action. This report also outlines the key means of implementation of the Platform for Action, along with the members’ and associate members’ delineated priorities for strengthening implementation and achieving gender equality.